State and civil society in Pakistan : politics of authority, ideology, and ethnicity - Malik, Iftikhar Haider, 1949- (Houndmills, Basingstoke, Hampshire : Macmillan Press ; New York : St. Martin's Press, 1997)
State and Civil Society in Pakistan analyses the enduring problems of governance as experienced in the predominantly Muslim polity of Pakistan in the context of an unequal relationship between the elitist state structure and weak civic institutions. The predicament is largely rooted in the unclear and mutually antagonistic relationship among the forces of authority, ideology and ethnicity.
Whereas manipulation of Islamic symbols by various regimes has exacerbated sectarianism, their own specific regionalist preferences (Muhajir and Punjabi earlier, and now with a visible Punjabi and Pushtun dispensation) have only politicized ethnicity. Volatile ethnic pluralism in Sindh and its criminalization in Karachi are the latest spectre of uneven politics in this country where successive governments have insisted on administrative rather than compact and consensus-based politico-economic measures.
Pakistan's difficulties with India help rationalize the continuity of an enormous defence establishment while significant areas like the judiciary, women's progress, education, health and press remain neglected, hampering the empowerment of civil society.
State and Civil Society: Conceptualisation -- 1. Dilemma of Political Culture, National Integration and Constitutionalism -- 2. Elite Formation, Politics of Ideology and Cooption -- 3. The Supremacy of the Bureaucracy and the Military -- 4. Feudalists in Politics: Trans-Regional Elitist Alliance -- 5. Unilateralism of the State: 'Invisible Government' at Work -- 6. State and Civil Society in Conflict -- 7. The Politics of Gender in Pakistan -- 8. Ethnicity, Nationalism and Nation-Building -- 9. Sindh: The Politics of Authority and Ethnicity -- 10. The Rise of the Muhajir Qaumi Movement and Ethnic Politics in Sindh.
"In association with St Antony's College Oxford."
Includes bibliographical references (p. 327-337) and index.
Keywords: Ethnicity -- Pakistan; Pakistan -- Politics and government; Pakistan -- Ethnic relations